Antimycobacterial and Anticancer Properties of Myrtus communis Leaf Extract - Mushtaq Ahmad Mir; Lamis Ahmad Memish; Serag Eldin Elbehairi; Nasreena Bashir; Faris Saif Masoud; Ali A. Shati; Mohammad Y. Alfaifi; Ahmad M. Alamri; Sultan Ahmad Alkahtani; Irfan Ahmad (MDPI AG, 2024)
Background: Plant-derived products or extracts are widely used in folk/traditional medicine to treat several infections, ailments, or disorders. A well-known medicinal herb, Myrtus communis is an evergreen fragrant plant native to the Mediterranean region that has been used for ages in traditional medicine around the world. Materials and methods: The microplate alamarBlue assay and the well diffusion method were used to evaluate the zone of inhibition and MIC, respectively. The double-disc diffusion method was used to investigate the synergy between antibiotics and the extract. The crystal violet method was used to investigate biofilm development. The SulphoRhodamine-B assay and DNA flow cytometry were used to investigate the proliferation and subsequent distribution of cells among different phases of the cell cycle. The apoptotic and necrotic phases of the cancer cells were examined using flow cytometry in conjunction with Annexin V-FITC/PI labeling. Using the IBM SPSS statistical program, a one-way ANOVA with Tukey's post hoc test was employed for statistical analysis. Results: The ethanolic leaf extract of M. communis showed a strong growth inhibition effect (zone of inhibition: 20.3 ± 1.1-26.3 ± 2.5 mm, MIC: 4.88-312.5 µg/mL, and MBC: 39.07-1250 μg/mL) against several rapidly growing and slow-growing mycobacterial strains in a dose-dependent manner. Damage to the cell wall of bacterial cells was determined to be the cause of the antimycobacterial action. The extract inhibited biofilm formation (MBIC of 9.7 µg/mL) and eradicated already-formed mature and ultra-mature biofilms of M. smegmatis, with MBEC values of 78 µg/mL and 156 µg/mL, respectively. Additionally, the extract exhibited potent anticancer effects against diverse cancer cell lines of the breast (MCF-7), liver (HepG2), cervix (HeLa), and colon (HCT116) (IC50 for HCT116: 83 ± 2.5, HepG2: 53.3 ± 0.6, MCF-7: 41.5 ± 0.6, and HeLa: 33.3 ± 3.6) by apoptosis after arresting the cells in the G1 phase of the cell cycle. Conclusions: These results suggest that M. communis leaf extract is a potential source of secondary metabolites that could be further developed as potential anticancer and antimycobacterial agents to treat diverse types of cancers and mycobacterial infections.